Dysphagia in the intensive care unit: epidemiology, mechanisms, and clinical management - Zuercher, Patrick; Moret, Céline S.; Dziewas, Rainer; Schefold, Joerg C. (Critical care (London, England), 2019)
Dysphagia may present in all critically ill patients and large-scale clinical data show that e.g. post-extubation dysphagia (PED) is commonly observed in intensive care unit (ICU) patients. Recent data demonstrate that dysphagia is mostly persisting and that its presence is independently associated with adverse patient-centered clinical outcomes. Although several risk factors possibly contributing to dysphagia development were proposed, the underlying exact mechanisms in ICU patients remain incompletely understood and no current consensus exists on how to best approach ICU patients at risk. From a clinical perspective, dysphagia is well-known to be associated with an increased risk of aspiration and aspiration-induced pneumonia, delayed resumption of oral intake/malnutrition, decreased quality of life, prolonged ICU and hospital length of stay, and increased morbidity and mortality. Moreover, the economic burden on public health care systems is high. In light of high mortality rates associated with the presence of dysphagia and the observation that dysphagia is not systematically screened for on most ICUs, this review describes epidemiology, terminology, and potential mechanisms of dysphagia on the ICU. Furthermore, the impact of dysphagia on affected individuals, health care systems, and society is discussed in addition to current and future potential therapeutic approaches.